A comparison of cutting technique performance in rugby union players - Green, B. S.; Blake, C.; Caulfield, B. M. (The Journal of Strength and Conditioning Research, 2011)
Rugby union is a dynamic running game requiring players to regularly perform change of direction maneuvers to avoid player opposition. The change of direction/cutting task is characterized by rapid deceleration onto the plant leg (PL) then reacceleration by the push-off leg (POL) into the new direction. Identification of the kinematic characteristics of cutting tasks and their relationship to playing ability may offer practical guidelines for coaches and strength and conditioning staff to design effective agility drills and provide player feedback to improve technique. Therefore, the purpose of this study was to investigate the kinematic and temporal characteristics of cutting tasks and their relationship to performance in rugby union players. Semiprofessional rugby union players from the All-Ireland League were placed in a Starters (N = 13) or Nonstarters (N = 10) group based on whether they were routinely selected in the starting team or were reserve `bench` players. Each participant was fitted with reflective markers and performed 10 cutting trials (5 left, 5 right) of a single 45° cutting task to collect relevant kinematic data. The directions of the cutting trials were classified as a dominant or nondominant cut based on the participant's dominant leg. All trials were then analyzed to determine the timings, angular displacements, and velocities during key events of the PL and POL in the cutting task. The total time to complete the cutting task was not statistically significant between groups; however, Starters demonstrated significantly shorter contact time of the PL during dominant cuts and initiated knee extension of the POL faster than Nonstarters in dominant and nondominant cuts. This preliminary study demonstrates that components of the cutting task differed between groups and may provide an insight for strength and conditioning professionals to assess change of direction technique.